Pengaruh Asam Laurat Terhadap Ukuran Nanopartikel Magnetit (Fe3O4) dari Pasir Besi Sijunjung - Milla Walfauziah Verina; Syamsi Aini (Natural Science, 2022)
Magnetite (Fe3O4) nanoparticles have been successfully synthesized from natural iron sand originating from the rest of the gold panning area of Sijunjung Regency, West Sumatra, Indonesia. The method used in this study is the coprecipitation method with the addition of lauric acid used to obtain a uniform particle size and to control the crystal size. With variations in the mass of lauric acid: 0 g, 1.25 g, 2.5 g, 3.75 g, and 5 grams. And variations in the mass of iron sand used are 8 g, 10 g, 12 g, 14 g, and 16 g. The difference in mass of iron sand produces a solution of FeCl3 and FeCl2 with different percentages of iron oxide solubility. The results of the synthetic powder tested by XRD on samples without the addition of lauric acid were dominated by the hematite phase and in samples with the addition of 1.25 g, 2.5 g, 3.75 g, and 5 grams of lauric acid, a cubic crystal structure with a single-phase magnetite was obtained. With the optimum conditions obtained in the Scherrer-Debay equation, it was obtained by adding 2.5 g of lauric acid with a crystal size of 22.3 nm